Developing performance-based measures of health literacy: A narrative case study and checklist of considerations. Issue 10 (October 2021) - Muscat, Danielle Marie; Costa, Daniel S.J.; Nutbeam, Don; McCaffery, Kirsten J.; Ayre, Julie
Highlights: We provide a checklist for developing performance-based health literacy instruments. Attempts should be made to assess a comprehensive range of health literacy skills. This includes assessment of critical appraisal, particularly of online information. Health literacy instruments should seek to impose minimal participant burden. Abstract: Research in health literacy is fundamentally impacted by our ability to adequately assess the construct. Although various measures of health literacy have been developed, there are few reflective discussions of the challenges and learnings from the instrument development process. This is somewhat surprising given that health literacy is a multi-dimensional and contested concept (with inherent measurement challenges), and that there are important practical considerations owing to the fact that people completing health literacy assessments may have lower general literacy (i.e. ability to read and write) and English-language skills. This paper discusses our learnings from developing a performance-based measure of parenting health literacy skills (the Parenting Plus Skills Index). The performance-based instrument is characterised by its grounding in health literacy as asset, with items spanning Nutbeam's functional, communicative and critical health literacy skills, and was designed chiefly to capture improvements resulting from health literacy skills training. This paper elucidates critical junctures in the development process, particularly regarding the conceptualisation and operationalisation of the construct. We also outline our approach to addressing practical measurement issues (e.g. administration time; item difficulty). In summarising these, we offer a 13-item checklist to inform the development of health literacy instruments for other health contexts or health conditions.